2016
DOI: 10.1080/10245332.2015.1101965
|View full text |Cite
|
Sign up to set email alerts
|

Increased regulatory T cells in acute lymphoblastic leukaemia patients

Abstract: Tregs in cancer are particularly significant in immunotherapy. The manipulation of the immune system to treat cancer has for a long time ignored regulatory mechanisms inducible or in place. In lymphoma studies, tumour-specific mechanisms that are unlike conventional methods in the induction of Tregs have been hypothesized. In addition, tumour-infiltrating Tregs may present different profiles from peripheral blood pictures. Tregs will continue to be dissected to reveal its mysteries and their impact on clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
1
23
0
2
Order By: Relevance
“…They play a central role in the maintenance of self‐tolerance and promote malignant cell progression by suppressing effective anti‐tumor immunity . In several different tumor entities, including hematological malignancies, a higher frequency of Treg was associated with an unfavorable clinical outcome . Hence, therapeutic options reducing Treg are encouraging treatment strategies for cancer control .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They play a central role in the maintenance of self‐tolerance and promote malignant cell progression by suppressing effective anti‐tumor immunity . In several different tumor entities, including hematological malignancies, a higher frequency of Treg was associated with an unfavorable clinical outcome . Hence, therapeutic options reducing Treg are encouraging treatment strategies for cancer control .…”
Section: Discussionmentioning
confidence: 99%
“…36 In several different tumor entities, including hematological malignancies, a higher frequency of Treg was associated with an unfavorable clinical outcome. [37][38][39][40][41] Hence, therapeutic options reducing Treg are encouraging treatment strategies for cancer control. 42,43 Antony et al 44 demonstrated that a CD8 + T cell immune response against antigens is hindered by Treg.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs play a central role in the maintenance of self-tolerance and promote malignant cell progression by suppressing effective antitumor immunity [14], and thus it is truly striking that clinical responders in the analyzed patient cohort show a significant reduction of Treg. Further studies detected an association with a higher frequency of Treg and unfavorable clinical outcome in several other tumor entities including hematological malignancies [15][16][17][18][19].…”
Section: Understanding the Functionality Of Dli-immunological Effectsmentioning
confidence: 90%
“…ACUTE lymphoblastic leukemia (ALL) is the most common malignancy diagnosed in children [1] . Patients with ALL receive intensive courses of chemotherapy which are followed by a period of leukopenia, Approximately three-quarters of patients express this common B-ALL precursor [2] .…”
Section: Introductionmentioning
confidence: 99%